Study on the Wear Resistance and Corrosion Resistance of Ni-Based WC Coatings on Wind Turbine Blades Prepared by Flame Spray Welding - WANG Xudong, ZHOU Youlong, CHEN Haoyu, LIU Jiawen, LIU Yu (Cailiao Baohu)
Wind turbine blades of coal-fired thermal power plants are not only subject to erosion from SOx and NOx due to incomplete desulfurization and denitrification during service， but also face corrosion from coastal salt spray.In addition， in the high-temperature flue gas atmosphere， the abrasion of wind turbine blades will be accelerated after collision with high ash corrosive particles in the combustion environment.In order to improve the corrosion resistance and wear resistance of wind turbine blades，the “two-step” oxygen -acetylene flame welding technology was used to prepared Ni60A ＋WC spray welded layers on the surface of Q355D low alloy steel substrate， and the wear resistance and corrosion resistance of spray welded layers with different mass fraction of WC hard phase in three corrosion solutions were evaluated by means of wear test and electrochemical test.Results showed that Ni60A＋WC spray welded layer could significantly improve the wear resistance and corrosion resistance of the wind turbine blades， and played a good protective role.When the mass fraction of WC hard phase was 65%Ni60A＋35%WC，the spray welded layer had the best wear resistance and corrosion resistance；Moreover，the spray welded layer had the best corrosion resistance to Cl－， but poor corrosion resistance to sulfides and nitrides.The initiation and propagation of cracks caused by high-speed particles and the formation of fatigue sources were the main mechanisms of wear failure in spray welded layers.In particular， the galvanic corrosion between hard phases and carbides and the substrate was the main corrosion mechanism of the spray welded layer， and the corrosion failure mode of the spray welded layer was selective corrosion.This work has certain reference significance for further extending the service life and cost saving of fan blades in thermal power plants.